2022
DOI: 10.1021/acscatal.2c01841
|View full text |Cite
|
Sign up to set email alerts
|

Microwave-Induced One-Pot Preparation of Bifunctional N-Fe/BC Catalysts and Oriented Production of Phenol-Enriched Bio-Oil from Biomass Pyrolysis: Catalyst Synthesis, Performance Evaluation, and Mechanism Insight via Theoretical Calculations

Abstract: To recover valuable products from biomass, bifunctional catalysts (N-Fe/BC) capable of microwave absorption and oriented production of phenolics were prepared by a one-pot method involving the microwave-induced K2FeO4. Its catalytic performances were evaluated, and the catalytic mechanism was explored using a model compound and DFT calculations. The cycle performance and deactivation mechanism were investigated. N-Fe/BC possessed a large S BET value (265.21 m2 g–1), good pore distribution, and abundant Fe and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 79 publications
0
3
0
Order By: Relevance
“…The Mn catalyst posted the strongest impeding synergy for aldehyde formation (−90.91%) for the 50:50 feed ratios. These observations indicated that the catalysts promoted deoxygenation reactions via demethoxylation, decarbonylation, dehydration, and decarboxylation routes. ,, However, for alcohol formations, all of the catalysts showed positive promotion synergy parameters and Zn-modified catalysts displayed the highest value (>175%), followed by Ni-catalysts (>80%) for all feed ratios. The increased promotion of alcohol formation may be attributed to reactions between the abstracted hydroxyl radical from the WS biomass and the alkyl radicals formed from the cracking of HDPE. ,, The synergistic parameter study results showed that the no-cat and catalytic copyrolysis process enhanced the synergy between WS and HDPE for producing valuable aromatic and α-olefin hydrocarbons and reduced the formation of oxygenates significantly.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…The Mn catalyst posted the strongest impeding synergy for aldehyde formation (−90.91%) for the 50:50 feed ratios. These observations indicated that the catalysts promoted deoxygenation reactions via demethoxylation, decarbonylation, dehydration, and decarboxylation routes. ,, However, for alcohol formations, all of the catalysts showed positive promotion synergy parameters and Zn-modified catalysts displayed the highest value (>175%), followed by Ni-catalysts (>80%) for all feed ratios. The increased promotion of alcohol formation may be attributed to reactions between the abstracted hydroxyl radical from the WS biomass and the alkyl radicals formed from the cracking of HDPE. ,, The synergistic parameter study results showed that the no-cat and catalytic copyrolysis process enhanced the synergy between WS and HDPE for producing valuable aromatic and α-olefin hydrocarbons and reduced the formation of oxygenates significantly.…”
Section: Resultsmentioning
confidence: 95%
“…Estimated Synergy Parameters for Copyrolysis Product Components indicated that the catalysts promoted deoxygenation reactions via demethoxylation, decarbonylation, dehydration, and decarboxylation routes. 6,14,19 However, for alcohol formations, all of the catalysts showed positive promotion synergy parameters and Zn-modified catalysts displayed the highest value (>175%), followed by Ni-catalysts (>80%) for all feed ratios. increased promotion of alcohol formation may be attributed to reactions between the abstracted hydroxyl radical from the WS biomass and the alkyl radicals formed from the cracking of HDPE.…”
Section: Metal Support Interaction and Basicity Analysismentioning
confidence: 97%
See 1 more Smart Citation